Habitat and adaptive foraging impacts on the topology and conservation of plant-pollinator interaction networks - Poyner, Heather Elizabeth (My University, 2025)
Plant-pollinator mutualistic interactions are crucial for maintaining global biodiversity. Therefore, it is important to identify the behaviors that confer stability to these communities by evaluating emergent patterns of community organization using network analysis for effective biodiversity conservation. In the U.S. Great Plains, habitat loss resulting from agricultural intensification has contributed to steep declines in pollinator populations. Private land conservation programs such as the Conservation Reserve Program (CRP) offer a potential solution to declining pollinator populations. However, most work has focused on bees with less effort to assess overall pollinator community structure in these conservation plantings. In addition to studying simple metrics of diversity, plant-pollinator network topology can provide insight into the behavior and ecological dynamics that structure these communities, such as adaptive foraging. Although theory has often implicitly assumed that plant-pollinator interactions are static, there is mounting evidence that pollinator species continually switch the plant species with which they interact to maximize energy gain per cost and enhance the efficiency of resource utilization. Pollinators may adapt their foraging choices to maximize mutualistic benefits or minimize competitive costs, but it is difficult to separate these influences on community structure and stability empirically. To address these issues, I performed empirical observations of plant-pollinator interactions on different CRP planting types as well as non-CRP grasslands and simulated plant-pollinator community dynamics with different adaptive foraging strategies. The objectives of this work were to: a) evaluate how local- and landscape-scale habitat characteristics influence the effectiveness of CRP planting types in supporting pollinator communities and b) examine how different adaptive foraging strategies and pollinator dependence on plants impact community stability and the resulting network topology in comparison to empirical networks. Pollinator community composition differed across CRP planting types, whereas pollinator abundance and diversity were more influenced by site-specific habitat characteristics, such as forb species richness and grassland habitat availability. Habitat characteristics had an interactive effect on pollinators such that landscape-scale habitat availability modulated the availability and diversity of pollinators that could use floral resources within CRP plantings. Plant-pollinator networks were specialized and modular, indicating that pollinator foraging decisions are guided more by niche partitioning in response to the abundance of competitors and the diversity of floral resources. In the simulation model, adaptive foraging resulted in less stable pollinator communities but larger pollinator populations, which suggests that without interaction switching interspecific competition kept pollinator populations at lower densities, but not so low as to result in competitive exclusion. Additionally, empirical network topology was most similar to that of simulated networks when pollinators were highly dependent on plants for survival. These findings offer insights into how the habitat characteristics of conservation plantings impact pollinator communities while highlighting the ecological dynamics that confer stability to plant-pollinator networks.
Keywords: Adaptive foraging; Conservation Reserve Program; Local and landscape habitat; Plant-pollinator interaction networks; Pollinator conservation